Role of Microbes in Human Health and Diseases - Singh Chauhan, Nar (IntechOpen, 2019)
Microbes are ubiquitous and have ecological interactions with almost all life forms. Likewise, humans invariably engage in host-microbial interactions that could induce short-term or long-term effects. Some of these long-term crossover interactions have allowed successful colonization of microbes within or on the human body, collectively known as the human microbiome or human microbiota. The human microbiome is identified as playing a key role in various physiological processes like digestion, immunity, defense, growth, and development. Any dysbiosis in the human microbiome structure could induce the onset of various metabolic or physiological disorders. Cumulatively, the human microbiome is considered as a virtual human organ that is essential for host survival. Additionally, short-term biological interactions of the host and microbes have exposed microbes to the human cellular system. This exposure could have allowed the microbes to invade human cells for their growth and reproduction-induced onset of various infectious diseases. This book incorporates a number of studies highlighting the role of microbes in human health and diseases.